THERAPEUTIC EFFICACY OF SODIUM ACID PHOSPHATE IN COMBINATION WITH DCP AND SSP IN HAEMOGLOBINURIC BUFFALOES - F. Deeba; M. R. Shahid; A. S. Qureshi (Journal of Animal and Plant Sciences, 2018)
This study was conducted to plan with the view to evaluate therapeutic efficacy of sodium acid phosphate in combination with Di-calcium phosphate (DCP) or single super phosphate (SSP) . Total 28 buffaloes were subjected to this study from Faisalabad and Lyaah. Animals were splitted into Groups A and B (n=14) . Group A; treated with sodium acid phosphate, (Inj.Alphos-40"), 200-250ml slow i/v b.i.d along with DCP @ 120g b.i.d. orally. Group B; treated with sodium acid phosphate (Inj.Alphos-40") 200-250 ml slow i/v b.i.d. and super juice @ 200mlb.i.d. orally. At the end of trial (7 days) blood samples were taken for serological tests. Phosphorous serum concentration was significantly (P<0.01) higher after the treatment in both groups than before the treatment. Similar trend was observed in total antioxidant system parameter but could not attain the optimal level as in healthy buffalo. Total cost on SSP given to one buffalo for 7 days was calculated to be low ( PKR 4.00) as compared to DCP ( P KR 90.78). The present study results indicate that super juice is effective as DCP, comparatively economical phosphorus supplement and acts as antioxidant in PHU affected buffaloes. 1982;Singariet al.,1991; Heuer and Bode,1998; Chhabra
Keywords: Di-calcium phosphate; super juice; total antioxidant status; phosphorus; buffaloes; parturient haemoglobinuria.